2020
DOI: 10.1504/ijsnet.2020.104463
|View full text |Cite
|
Sign up to set email alerts
|

A MQTT-API-compatible IoT security-enhanced platform

Abstract: Owing to its lightweight and easiness, the message queue telemetry transport (MQTT) has become one of the most popular communication protocols in the internet-of-things (IoT). However, the security supports in the MQTT are very weak. In this paper, we systematically examine the security requirements of a MQTT-based IoT system, identify the gap between the requirements and the supported functions, and design a security-enhanced MQTT framework. The framework facilitates device authentication, key agreement, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…In contrast to the CoAP Request/response approach, it employs the publish/subscribe mechanism, which is better suited for the IoT. Furthermore, despite the availability of newer protocols, such as MQTT [ 112 ], it is an early internet protocol that has been supported. It is based on the Internet Engineering Task Force (IETF) standards for cross messaging, telepresence, and video and audio calling [ 113 ].…”
Section: Iomt Architecture Systemmentioning
confidence: 99%
“…In contrast to the CoAP Request/response approach, it employs the publish/subscribe mechanism, which is better suited for the IoT. Furthermore, despite the availability of newer protocols, such as MQTT [ 112 ], it is an early internet protocol that has been supported. It is based on the Internet Engineering Task Force (IETF) standards for cross messaging, telepresence, and video and audio calling [ 113 ].…”
Section: Iomt Architecture Systemmentioning
confidence: 99%
“…All included MQTT clients can send and receive messages within a related channel, named a topic. The MQTT broker(s), on the other hand, is responsible for distributing messages coming from publisher clients to the subscriber clients (and to other devices, if any), depending on the topics they are interested in [20]. Mosca JS, an MQTT brokerage system, is preferred for broker implementation due to its simplicity and ease of use (as well as potential performance benefits).…”
Section: Message Transmission Protocolmentioning
confidence: 99%
“…Some proposals like [40] propose authenticated key agreement schemes for MQTT systems. Chien et al [41] proposed a two-phase authentication framework in which any secure key agreement scheme can be performed in the first phase, and then the hash value of the session key is supplied as a password in the second phase MQTT CONNECT API. Chien [35] proposed an anonymous IoT protocol in the MQTT 3.11 CONNECT API.…”
Section: Related Workmentioning
confidence: 99%
“…In this section, we describe how we can apply our proposed D2S anonymous scheme in the MQTT 5.0 context. Chien et al [41] has shown how to implement their two-phase challenge-response protocol for enhancing the MQTT authentication, using the MQTT v3.1 [43] CONNECT API. The new MQTT standards v5.0 [5] has extended the MQTT v.3.1 API to incorporate a new feature called the enhanced authentication.…”
Section: Using Our D2s Anonymous Scheme In the Mqtt 50 Contextmentioning
confidence: 99%